PREOPERATIVE HEALTH-RELATED QUALITY OF LIFE IN PATIENTS UNDERGOING ELECTIVE SURGERY FOR COLORECTAL CANCER - Nikolic, Vladimir; Kmezic, Stefan; Antic, Andrija; Knezevic, Djordje; Markovic-Denic, Ljiljana (Medical Research, 2026)
Introduction/Aim: Health-related quality of life (HRQoL) is an important multidimensional, patient-centered concept in colorectal cancer (CRC). However, data on preoperative HRQoL in Southeast European surgical populations remain limited. The aim of this study was to describe preoperative HRQoL in patients undergoing elective surgery for CRC, compare HRQoL between colon and rectal cancer, and identify sociodemographic and clinical factors associated with preoperative HRQoL.Material and Methods: Preoperative HRQoL was assessed using the Functional Assessment of Cancer Therapy–Colorectal (FACT-C) and the Cleveland Clinic Colorectal Cancer Quality of Life questionnaire (CCF-CaQL). Sociodemographic and clinical data were collected using a structured questionnaire and medical records. Group comparisons were performed according to tumor localization, while factors associated with FACT-C total score were evaluated using univariable and multivariable linear regression.Results: The mean CCF-CaQL total score was 92.3±20.4, and the mean FACT-C total score was 98.8±18.2. No significant differences in HRQoL were observed between patients with colon and rectal cancer across any questionnaire domains (all p>0.05). In multivariable analysis, higher ASA physical status was independently associated with lower FACT-C total score (B=-5.05; 95% CI -9.70 to -0.40; p=0.033).Conclusion: Preoperative HRQoL in patients undergoing elective CRC surgery was moderate and did not differ significantly by tumor localization. Higher ASA physical status was independently associated with poorer preoperative HRQoL.
Keywords: colorectal cancer; quality of life; FACT-C; CCF-CaQL; preoperative assessment